2002
DOI: 10.1002/bit.10433
|View full text |Cite
|
Sign up to set email alerts
|

Structural and catalytic response to temperature and cosolvents of carboxylesterase EST1 from the extremely thermoacidophilic archaeon Sulfolobus solfataricus P1

Abstract: The interactive effects of temperature and cosolvents on the kinetic and structural features of a carboxylesterase from the extremely thermoacidophilic archaeon Sulfolobus solfataricus P1 (Sso EST1) were examined. While dimethylformamide, acetonitrile, and dioxane were all found to be deleterious to enzyme function, dimethyl sulfoxide (DMSO) activated Sso EST1 to various extents. This was particularly true at 3.5% (v/v) DMSO, where k(cat) was 20-30% higher than at 1.2% DMSO, over the temperature range of 50-85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It has been reported that purified microbial and metagenomic esterases exhibit different sensitivities to organic solvents and detergents (Elend et al 2006;Fu et al 2011;Jiang et al 2012;Kang et al 2011). For example, the activity of the EstA esterase from Arthrobacter nitroguajacolicus was slightly stimulated (10-20 %) by the addition of DMSO (30 %) or acetonitrile (30 %), whereas lower concentrations (10 %) of these solvents reduced (20 to 90 %) the activity of esterases from Sulfolobus solfataricus (EST1) and Archaeoglobus fulgidus (Est-AF) (Kim et al 2008;Schutte and Fetzner 2007;Sehgal et al 2002). Similarly, several metagenomic esterases have been reported to be inhibited, unaffected or stimulated by the addition of DMSO (10-30 %), whereas all these enzymes were sensitive to acetonitrile and detergents (Triton X-100 and Tween-20) (Elend et al 2006;Fu et al 2011;Jiang et al 2012;Kang et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that purified microbial and metagenomic esterases exhibit different sensitivities to organic solvents and detergents (Elend et al 2006;Fu et al 2011;Jiang et al 2012;Kang et al 2011). For example, the activity of the EstA esterase from Arthrobacter nitroguajacolicus was slightly stimulated (10-20 %) by the addition of DMSO (30 %) or acetonitrile (30 %), whereas lower concentrations (10 %) of these solvents reduced (20 to 90 %) the activity of esterases from Sulfolobus solfataricus (EST1) and Archaeoglobus fulgidus (Est-AF) (Kim et al 2008;Schutte and Fetzner 2007;Sehgal et al 2002). Similarly, several metagenomic esterases have been reported to be inhibited, unaffected or stimulated by the addition of DMSO (10-30 %), whereas all these enzymes were sensitive to acetonitrile and detergents (Triton X-100 and Tween-20) (Elend et al 2006;Fu et al 2011;Jiang et al 2012;Kang et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Enzyme-catalyzed reactions in organic solvents, and even in supercritical fluids and the gas phase, have found numerous potential applications, some of which have already been commercialized. DMSO was reported to have an activating effect related to small changes in the enzyme's structure, resulting in an increase in its conformational flexibility [40]. Thus, co-solvents may also serve as activators in applications, in addition to their use for solubilizing hydrophobic substrates in water.…”
Section: Discussionmentioning
confidence: 99%
“…1). This observation points to the heightened structural rigidity of hyperthermophilic enzymes, even within their functional temperature ranges [48]. All XIs are known to be active only in the presence of divalent cations.…”
Section: Discussionmentioning
confidence: 99%